2016
DOI: 10.1016/j.renene.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heliostat curvature on optical performance of Linear Fresnel solar concentrators

Abstract: a b s t r a c tThe present paper gives a numerical investigation of the effect of mirror curvature on optical performance of a Linear Fresnel Reflector solar field installed recently in Morocco. The objective is to highlight and discuss the effect of mirror curvature on the flux density distribution over the receiver and the system optical efficiency. For this purpose, a Monte Carlo-ray tracing simulation tool is developed and used to optimize the optical design taking into account the curvature degree of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…18 It has been found that curvature impact on LFR efficiency is inversely proportional to receiver height and that deflection coefficient varying between 1 and 2 mm is sufficient enough to achieve high concentration ratio. 18 It has been found that curvature impact on LFR efficiency is inversely proportional to receiver height and that deflection coefficient varying between 1 and 2 mm is sufficient enough to achieve high concentration ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 It has been found that curvature impact on LFR efficiency is inversely proportional to receiver height and that deflection coefficient varying between 1 and 2 mm is sufficient enough to achieve high concentration ratio. 18 It has been found that curvature impact on LFR efficiency is inversely proportional to receiver height and that deflection coefficient varying between 1 and 2 mm is sufficient enough to achieve high concentration ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Benyakhlef et al have numerically investigated the impact of mirror curvature on optical performances of an LFC through the use of a Monte Carlo-ray tracing simulation tool. 18 It has been found that curvature impact on LFR efficiency is inversely proportional to receiver height and that deflection coefficient varying between 1 and 2 mm is sufficient enough to achieve high concentration ratio. Mokhtar et al developed a mathematical model for the estimation of the thermal efficiency of a small-scale LFC, assuming that the optical efficiencies of the collector are a function of declination angle and sun altitude.…”
Section: Discussionmentioning
confidence: 99%
“…The annual energy losses due to cosine effect from the East-West-oriented LFR field is about 30 % higher than that of North-South-oriented field for Murcia (38.2°N, 1.6°W), Spain (Sharma et al 2015b). Benyakhlef et al (2016) investigated the impact of curved mirrors for LFR field using a Monte Carlo-ray tracing simulation tool and concluded that the curved mirrors lead to better optical performance and flux density onto the receiver than the flat mirrors. It was also reported that the curvature impact on the LFR efficiency is inversely proportional to the receiver height, and therefore, in case of the higher receiver height, the optical efficiency is less affected by the mirror curvature.…”
Section: Linear Fresnel Reflectormentioning
confidence: 99%
“…In case of flat mirrors, changing the receiver height from 2 to 6 m increases the optical efficiency of the system up to 10 %. Moreover, deflections in the mirrors of about 3 mm allow decrease in the size of the receiver (Benyakhlef et al 2016). If the mirror curvatures are designed with the sun as specific reference, an increase in the power output of about 1.2 %, compared to the same solar collector aperture area with flat mirrors, can be achieved .…”
Section: Linear Fresnel Reflectormentioning
confidence: 99%
“…Balaji et al (2016) employed the combination of multi-stage focusing and multiple reflectors to increase the concentration ratio and also to improve the flux distribution over the circumference of the absorber [18]. Benyakhlef et al (2016) used multiple rotating curved heliostats instead of flat ones to reflect the sun-rays onto the linear receiver at a fixed position. Primary focusing heliostats were arranged in rows whereas the secondary reflector was only one reflector.…”
mentioning
confidence: 99%